2014
DOI: 10.1124/dmd.114.060145
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Production of Novel Pre-MicroRNA Agent hsa-mir-27b in Escherichia coli Using Recombinant RNA Technology for Functional Studies in Mammalian Cells

Abstract: Noncoding microRNAs (miRNAs or miRs) have been revealed as critical epigenetic factors in the regulation of various cellular processes, including drug metabolism and disposition. However, research on miRNA functions is limited to the use of synthetic RNA and recombinant DNA agents. Herein, we show that novel premiRNA-27b (miR-27b) agents can be biosynthesized in Escherichia coli using recombinant RNA technology, and recombinant transfer RNA (tRNA)/mir-27b chimera was readily purified to a high degree of homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 40 publications
(53 reference statements)
1
70
0
Order By: Relevance
“…Recombinant ncRNAs were expressed in HST08 as described (Ponchon and Dardel, 2007;Ponchon et al, 2009;Li et al, 2014). Total RNAs were isolated using the Tris-HCl-saturated phenol extraction method, quantitated with a NanoDrop 2000 spectrophotometer (Thermo Fisher Scientific), and analyzed by denaturing urea (8 M) PAGE (8%) to assess the expression of recombinant ncRNAs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant ncRNAs were expressed in HST08 as described (Ponchon and Dardel, 2007;Ponchon et al, 2009;Li et al, 2014). Total RNAs were isolated using the Tris-HCl-saturated phenol extraction method, quantitated with a NanoDrop 2000 spectrophotometer (Thermo Fisher Scientific), and analyzed by denaturing urea (8 M) PAGE (8%) to assess the expression of recombinant ncRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…qRT-PCR was conducted with qRT-PCR Master Mix (New England Biolabs) on a CFX96 Touch real-time PCR system (Bio-Rad), as described (Bi et al, 2014;Li et al, 2014). The primers were as follows: 59-GGC TAC GTA GCT CAG TTG GT-39 (forward) and 59-TGG TGG CTA CGA CGG GAT TC-39 (reverse) for chimeric ncRNAs; 59-GGC CAG CTG TGA GTG TTT CTT TGG-39 (forward) and 59-GGG CCC CAC AAC GTG CAG-39 (reverse) for premiRNA mir-34a; 59-CGC GCT GGC AGT GTC TTA GCT-39 (forward) and 59-GTG CAG GGT CCG AGG T-39 (reverse) for mature miR-34a; and 59-CTC GCT TCG GCA GCA CA-39 (forward), and 59-AAC GCT TCA CGA ATT TGC GT-39 (reverse) for U6.…”
Section: Biologic Mir-34a As Anticancer Prodrugmentioning
confidence: 99%
“…Expression of tRNA/mir-1291 chimeras and the control tRNA/MSA was performed as described (Ponchon and Dardel, 2007;Ponchon et al, 2009;Li et al, 2014). In brief, freshly transformed HST08 E. coli cells (Clontech, Mountain View, CA) were plated on a Lysogeny broth (LB) agar plate containing 100 mg/ml of ampicillin.…”
Section: Methodsmentioning
confidence: 99%
“…In an effort to address the gap in understanding posttranscriptional gene regulation mechanisms underlying variable drug metabolism, many studies have demonstrated that some CYP genes may be regulated by miRNAs in human cell line model systems (Table 1). Among them, a well-conserved miRNA miR-27b was shown to directly act on multiple CYPs including CYP1B1 and CYP3A4 (Tsuchiya et al, 2006;Pan et al, 2009a;Li et al, 2014b). Luciferase reporter assays were first employed to define the interactions of miR-27b with corresponding MRE sites within the 39UTRs of CYP1B1 in MCF-7 and CYP3A4 in HEK-293 cells, which were predicted by bioinformatic algorithms.…”
Section: Micrornas In Posttranscriptional Gene Regulationmentioning
confidence: 99%